Analysis of The Effect of Variations in Mud Content on Stability and Flow Values in Asphalt Concrete Mixtures Layer Aus (AC-WC) - Safridatul Audah; Adrian Kaifah; Sulaiman AR; Meraty Ramadhini (Jurnal Inotera, 2023)
Aggregat mud affect the weakening of asphalt adhesion and bonds between aggregate grains which will cause damage more quickly before reaching the design age, one of which is the formation of holes in the road surface layer.The purpose of this study was to measure the effect of variations in silt content on the stability and flow values ​​of Asphalt-coated concrete mix (AC-WC). All tests were carried out using the Marshall test method and each test object became the basis for calculations to analyze the stability and flow values ​​of the AC-WC asphalt concrete mixture with variations in silt content of 0%, 5%, 10%, 15% and 20%. The optimal bitumen content used is 6.7%. Furthermore, marshall testing was carried out on variations in silt content in the aggregate to obtain stability and flow values, stability values ​​tended to decrease from 1048.64 kg to 798.96 kg, this affected the minimum stability value of ≥ 800 kg and flow values ​​tended to increase from 1.54 mm to 3.05 mm, but the discharge value still meets the required limit of ≥ 3 mm with a mud content of 13%. Based on the results of the ANOVA analysis obtained from the test, the stability value shows a significant decrease in the level of stability and the flow value shows an insignificant effect on the proportion of sludge.